A Review of Approaches to Empirical Research on the Resource-Based View of the Firm† - Armstrong, Craig E.; Shimizu, Katsuhiko (Journal of Management, 2007)
This study reviews empirical studies of the resource-based view (RBV) and examines methodological issues and new directions that will help to clarify the value and boundaries of the RBV. Through our comprehensive review of the research design and operationalization of resource-based constructs used in 125 empirical studies, we (1) discuss key empirical issues particularly important to RBV research, (2) illustrate how researchers have or have not overcome some of these challenges, and (3) highlight two important approaches that offer promise for sharpening the boundary conditions of the RBV: an integrative framework for RBV research and utilization of nonsignificant results.